Membangun Generasi Emas 2045: Sinergi Pemberian Makanan Tambahan dan Digitalisasi Data dalam Pencegahan Stunting di Kabupaten Jember - Robby Reza Zulfikri; Sjafruddin; Hendrik Tri Oktaviansyah; Bahrina Almas; Inayah Swasti Ratih (Jurnal Solusi Masyarakat (JSM), 2026)
Stunting remains a major health problem in Indonesia, impacting the quality of future human resources. Stunting prevention efforts require a comprehensive and collaborative approach, particularly at the village level. This community service program aims to improve knowledge, promote clean and healthy living behaviors (PHBS), and utilize digital data to support stunting prevention in Sukowono Village, Jember Regency. The methods used include education for mothers of toddlers and integrated health post (Posyandu) cadres, provision of locally-based supplementary feeding (PMT), and training in digitalizing health data to improve the accuracy and monitoring of children's nutritional status. The results of the program indicate an increase in community knowledge regarding nutrition and PHBS, increased participation in Posyandu activities, and the availability of a more orderly and integrated data recording system. The synergy between nutrition interventions, behavioral change, and the use of digital technology has proven effective in supporting stunting prevention efforts. This program is expected to become a sustainable model for realizing a healthy and quality generation towards Indonesia Emas 2045.